2012
DOI: 10.1186/1471-2407-12-94
|View full text |Cite
|
Sign up to set email alerts
|

Fibronectin matrix-mediated cohesion suppresses invasion of prostate cancer cells

Abstract: BackgroundInvasion is an important early step in the metastatic cascade and is the primary cause of death of prostate cancer patients. In order to invade, cells must detach from the primary tumor. Cell-cell and cell-ECM interactions are important regulators of cohesion - a property previously demonstrated to mediate cell detachment and invasion. The studies reported here propose a novel role for α5β1 integrin - the principle mediator of fibronectin matrix assembly (FNMA) - as an invasion suppressor of prostate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 32 publications
0
33
0
Order By: Relevance
“…This protein has been found to be expressed in BC [40, 41], and other cancers [37, 42, 43]. Moreover, it has been reported that FN could induce progression of various cancer cells [36, 37] and is strongly expressed in breast carcinoma, and its distribution is different from that of normal breast parenchyma [38, 39].…”
Section: Discussionmentioning
confidence: 99%
“…This protein has been found to be expressed in BC [40, 41], and other cancers [37, 42, 43]. Moreover, it has been reported that FN could induce progression of various cancer cells [36, 37] and is strongly expressed in breast carcinoma, and its distribution is different from that of normal breast parenchyma [38, 39].…”
Section: Discussionmentioning
confidence: 99%
“…The ability of prostate cancer cells to assemble a fibronectin matrix is correlated with the ability to form cohesive aggregates and cellular α 5 β 1 expression. High α 5 β 1 levels and fibronectin matrix assembly are inversely correlated with invasiveness; loss of α 5 β 1 allows cell detachment, leading to intravasation and metastasis [116]. Agonism of α 5 β 1 has therefore been proposed as an anti-metastatic strategy and the MEK inhibitor AZD6244 has been shown to promote cell adhesion, possibly by activating α 5 β 1 [116], however such an approach will require careful assessment for safety, since α 5 β 1 -mediated adhesion and angiogenesis could promote the establishment of metastases once cells have detached from the main tumour.…”
Section: Consequences Of Integrin Expression In Prostate Cancermentioning
confidence: 99%
“…High α 5 β 1 levels and fibronectin matrix assembly are inversely correlated with invasiveness; loss of α 5 β 1 allows cell detachment, leading to intravasation and metastasis [116]. Agonism of α 5 β 1 has therefore been proposed as an anti-metastatic strategy and the MEK inhibitor AZD6244 has been shown to promote cell adhesion, possibly by activating α 5 β 1 [116], however such an approach will require careful assessment for safety, since α 5 β 1 -mediated adhesion and angiogenesis could promote the establishment of metastases once cells have detached from the main tumour. Recent work has shown that the actin regulatory protein Mena is required for α 5 β 1 -mediated functions and signalling in fibroblasts [117].…”
Section: Consequences Of Integrin Expression In Prostate Cancermentioning
confidence: 99%
“…showed that only wild-type, fully functional α5β1 integrin could promote FNMA by CHO cells and that only a fully developed fibronectin matrix could give rise to increased intercellular cohesion [48]. The concepts and methods underlying integrin–ECM-based cohesion have now been applied to studies of malignant invasion in various cancer models, including prostate cancer [49] and, more pertinent to this article, GBM [50]. In both models, ECM-based cohesion appears to be correlated with FNMA and could be pharmacologically induced by treatment with dexamethasone.…”
Section: Integrins As Mediators Of Cell-cell Cohesionmentioning
confidence: 99%